2017
DOI: 10.1016/j.stemcr.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide Analysis of Human Pluripotent Stem Cell-Derived Endothelial Cells in 2D or 3D Culture

Abstract: SummaryA defined protocol for efficiently deriving endothelial cells from human pluripotent stem cells was established and vascular morphogenesis was used as a model system to understand how synthetic hydrogels influence global biological function compared with common 2D and 3D culture platforms. RNA sequencing demonstrated that gene expression profiles were similar for endothelial cells and pericytes cocultured in polyethylene glycol (PEG) hydrogels or Matrigel, while monoculture comparisons identified distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 72 publications
4
55
2
Order By: Relevance
“…4 One comprehensive genome-wide study comparing iPSC-ECs grown in 2D or 3D substrates revealed that iPSC-ECs developed in 2D adopt a more proliferative phenotype characterized by increased focal adhesion kinase (FAK)–extracellular signal-regulated kinase (ERK) activity, in which inhibition of ERK signaling increased the expression of vasculature development genes. 57 Therefore, it is possible that the difference in signal transduction dynamics between integrins and cell adhesion kinases in 2D versus 3D contributes highly to endothelial differentiation capacity and cellular organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 One comprehensive genome-wide study comparing iPSC-ECs grown in 2D or 3D substrates revealed that iPSC-ECs developed in 2D adopt a more proliferative phenotype characterized by increased focal adhesion kinase (FAK)–extracellular signal-regulated kinase (ERK) activity, in which inhibition of ERK signaling increased the expression of vasculature development genes. 57 Therefore, it is possible that the difference in signal transduction dynamics between integrins and cell adhesion kinases in 2D versus 3D contributes highly to endothelial differentiation capacity and cellular organization.…”
Section: Discussionmentioning
confidence: 99%
“…33,57 We hypothesized that endothelial differentiation directly within topographically aligned 3D scaffolds may be a facile one-step approach to generate iPSC-ECs with aligned network-like organization to mimic that of myocardial microvasculature.…”
Section: Introductionmentioning
confidence: 99%
“…5f) and GSE93511(2D_MG_H1EC and 2D_MG_HUVEC ) ( Fig. 5e) [26], these genes including CD43(SPN), CD45 (PTPRC) and PROM1 which express in early-EPC have some expression. Thus, we think conservatively that normal EPCs, IPAH-EPCs and ESC/iPSC-ECs we obtained have characteristics of early EPCs.…”
Section: Results Showed Ecs On Day 7 With Higher Expression Level Of mentioning
confidence: 94%
“…A high-efficiency protocol for deriving ECs from ESCs or iPSCs has been published [26], we optimized the protocol according to other protocols [15,25,29], we seeded about 3 × 10 4 cells/well in 12-well plate using 10 µM Y27632 and 10 ng/mL BMP4 for the three days (Fig. 1a, b and c).…”
Section: A Modified Protocol For Generating Ecs From Human Escs or Ipscsmentioning
confidence: 99%
See 1 more Smart Citation